Aspek Olahraga Dalam Kesenian Tradisional Gantao - Erwin Erwin (Lembaga Penelitian dan Pendidikan Mandala, 2020)
Gantao traditional art is a culture that is rooted in Bima society - from generations of generation, the existence of traditional gantao art proves that the Bima region has a culture that upholds the values of life in society. In the historical record of gantao traditional art is an uptake culture from Sulawesi that enters Bima via shipping lines and inter-island trade to form cultural acculturation between Bima and Sulawesi. Traditional gantao art is not just an ordinary culture in the form of performances of martial arts movements but has very broad aspects and values in people's lives. one of the aspects contained in gantao art is sport. This discussion uses descriptive qualitative methods by relying on in-depth observations and analyzes related to the relationship between traditional gantao art and sports. The results of the discussion obtained are that there are aspects of sport in the movements contained in the traditional gantao art.